Postacute Sequelae of COVID-19 in Pediatric Patients Within the United States: A Scoping Review - Christine M. Miller; Carla Borre; Alex Green; Melissa Funaro; Carlos R Oliveira; Akiko Iwasaki (American Journal of Medicine Open)
A subset of children and adolescents experience recurrent or persistent symptoms following SARS-CoV-2 infection, known as postacute sequelae of COVID-19 (PASC), however, the clinical epidemiology within the United States (US) is not yet well understood. This scoping review aims to synthesize the clinical epidemiology of pediatric PASC in the US. A comprehensive literature search was conducted and databases were queried from inception until January 29, 2024. Studies including US children and adolescents <21 years old were considered. From 1028 studies identified, 29 met the inclusion criteria. Prevalence of PASC ranged from less than 1%-27%. Risk factors included older age, female sex, asthma, obesity, and severe initial infection. Common symptoms were dyspnea, fatigue, headaches, and chest pain. A multidisciplinary approach for diagnosis and management was common across studies. Most studies had a high risk of bias and were limited by a lack of standardized definitions and short follow-up duration. This review establishes a foundation for understanding pediatric PASC and highlights the critical need for continued research to optimize prevention and treatment strategies.